Correlation of Vitamin D and Calcium Levels in Children in New Diagnosed Epilepsy and Minimal 6 Months After Therapy - Niluh Suwasanti; Aryati Aryati; Darto Saharso; Ferdy Royland Marpaung (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
INTRODUCTION. Children with epilepsy should take long-term anti-epileptic drugs. Long-term use of anti-epileptic drugs can reduce vitamin D levels. Low vitamin D will lead to low blood calcium levels. This study aims to analyze the relationship between vitamin D and calcium levels in newly diagnosed epileptic children and ≥6 months after therapy. METHOD. These was an analytical observational study with cross sectional research design. The vitamin D examination instrument uses the ELFA method (enzyme linked fluorescent assay) with the Vidas instrument from bioMerieux. Samples were collected during June - August 2018 from Inpatient and Outpatient Clinics. The samples were divided into new diagnosis of epilepsy group and 6 months after therapy group. Each group was measured for vitamin D and serum calcium levels. The relationship between the two parameters were analyzed using T-Test independent. RESULTS. From the 19 new diagnosis of epilepsy, there were 57.9% low vitamin D and 10.5% low calcium levels. From the 20 subjects 6 months after therapy, 70% low vitamin D and 25% low calcium levels. There were a relationship between vitamin D and calcium levels in patients with newly diagnosed and ≥6 months after therapy. DISCUSSION. Low vitamin D and low calcium levels were found more in the anti-epileptic therapy group than the new diagnosis group of epilepsy. Low vitamin D levels can be caused by the use of long-term antiepileptic drugs that will affect serum calcium levels. CONCLUSION. This study showed a significant relationship between vitamin D and serum calcium levels in patients with newly diagnosed epilepsy and 6 months after therapy. Vitamin D and calsium serum examination should be done in every patient who gets long term therapy of antiepileptic drugs. KEY WORDS. Vitamin D, calcium, epilepsy, ELFA.